Determination of the Genotoxic Potential of Annatto Seed by Single Cell Gel Electrophoresis in Layer- Hen - Bushra M.W. Al-Obaidi (Journal of Global Pharma Technology, 2016)
The aimed of this study is to investigation the toxicity of annatto seeds added to the diet of layer hens for different level. A total of 240 Lohmann hens 67 week of ages for 12 weeks were distributed randomized blocks into four treatments (60 hens) with three replicates 20 hens of each. The following treatments were applied: T1- control feed on based die; T2- feed on Annatto seed at 75gm/100kg, T3- feed on Annatto seed at 150gm/100kg, T4- feed on Annatto seed at 225gm/100gm. In the end of study blood samples were collected from 9 birds from each group from the wing vein in a test tube with coagulant for cytogenetic parameters. The result demonstrated that 2nd group recorded maximum significant (p≤0.05) differences compared to other nourished groups in all comet assay parameters(%DNA in head, Tail length,% DNA in tail, Tail moment and Olive tail moment) then followed by T3 regressed maximum significant (p≤0.05) differences of comet length. T1, T4 recorded a significant (p≤ 0.05) decrement in comet assay parameter respectively compared with other studied groups. The addition of Annatto seed at 225gm / 100kg to the diet of layer hens has an adverse effect on blood lymphocyte and cases highly damage of DNA, while added at level 75gm/kg(T2) and 150 gm/kg(T3)which protect lymphocyte from damage as shown in comet assay parameters.Keywords: Annatto seed, Single Cell Gel Electrophoresis (comet assay), Layer.